Answer:
[tex]\boxed{\tt \: f( - 6) = 4}[/tex]
Step-by-step explanation:
Given polynomial :-
[tex] \sf \: f(x) = - x - 2[/tex]
To Find :-
[tex] \sf \: f( - 6)[/tex]
Solution :-
[tex]\sf \implies \: f(x) = - x - 2[/tex]
[tex]\underline{ \rm \: Substitute \: the \: value \: of \: x \: that \: is \: 6 \: i nstead \: of \: x \: on \: the \: LHS \: and \: RHS \: of \: the \: given \: equation :-}[/tex]
That is ,
[tex]\sf \implies \: f( - 6) = - ( - 6) - 2[/tex]
[tex]\underline{ \rm \: Simplify \: the \: RHS \: on \: t he \: given \: equation :-}[/tex]
As we know that "-" and "-" equals to "+". So "-(-6)" would be represented as +6 (6).
[tex]\sf \implies \: f( - 6) = + 6 - 2[/tex]
Subtract 6 and 2 :-
[tex]\sf \implies \: f( - 6) = 6 - 2[/tex]
[tex]\sf \implies \: f( - 6) = 4[/tex]
This can't be simplified more . Hence ,
[tex] \rm \: The \: value \: of \: f(-6) \: would \: be \: \boxed{ \bf 4} \rm .[/tex]
[tex] \rule{175pt}{2pt}[/tex]
I hope this helps!